TELAAH KITAB AYYUHAL WALAD: PENDIDIKAN KARAKTER ISLAMI DALAM PERSPEKTIF PEMIKIRAN IMAM AL-GHAZALI - siregar, Muhammad irfanysah; Karim, Pangulu Abdul (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2024)
This study aims to find out Imam al-Ghazali's thoughts on character education, character education materials, and character education methods as stated by al-Ghazali in his book entitled Ayyuhal Walad. This research is motivated by the widespread news that shows the weakening of students' morals and characters, such as brawls, bullying, crime, and even drug abuse. As a result, education, which basically has one of its objectives to shape the morals of students, is required to provide solutions to the weakening of students' morals and characters. Character education is needed to answer all existing problems by continuing to develop and improve materials and methods so that it can achieve the main goal of creating students who are morally upright. The process of developing and improving character education can be done by analyzing the thoughts of scholars who have a concern about character and morals, one of whom is al-Ghazali in his book entitled ayyuhal walad. This research uses a qualitative research method with the type of library research or library research which makes the book ayyuhal walad as the primary data source and books, journals, and relevant research as secondary sources. The results of this study show that in creating akhlakul karimah in students, it is necessary to instill the purification of intention, a sense of solidarity, hard work, simplicity, and brotherhood.